The impact of human resources strategies in the General Presidency for the Affairs of the Holy Mosque (Al-masjid Al-haram) on the extent to which it achieves the Kingdom’s Vision 2030 (International Journal of Financial, Administrative and Economic Sciences, 2024)
The research aims at strategic planning for human resources. The results showed that the General Presidency applies strategies aimed at improving job performance, such as continuous training, leadership development, and modern technologies. It was found that there is a significant investment in digital transformation, which supports process automation and improves efficiency. It became clear that the Presidency faces challenges in areas such as job localization and achieving a balance between employee needs and the organization's goals. It also showed that training programs aimed at achieving the standards of Vision 2030 were enhanced, especially in the areas of leadership and visitor service. The study also aims to increase focus on motivation strategies to enhance job satisfaction and productivity. The Presidency seeks to improve recruitment and professional development mechanisms to ensure attracting the best competencies and localizing jobs. With the continuation of performance evaluation and linking results to indicators for measuring the goals of Vision 2030. It became clear that the Presidency plays a pivotal role in human resources strategies in enabling the General Presidency for the Affairs of the Grand Mosque to contribute to achieving the Kingdom's Vision 2030. However, it requires continuous review of these strategies to ensure adaptation to national and international variables and requirements.
Keywords: Human Resources Strategies; General Presidency for the Affairs of the Grand Mosque; Kingdom's Vision 2030